2005
DOI: 10.1090/s0002-9947-05-04097-3
|View full text |Cite
|
Sign up to set email alerts
|

Limiting weak–type behavior for singular integral and maximal operators

Abstract: Abstract. The following limit result holds for the weak-type (1,1) constant of dilation-commuting singular integral operatorFor the maximal operator M , the corresponding result is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…(3.5) is true for centered Hardy-Littlewood maximal function. On the other hand, using the limiting weak type behavior for maximum function in [7], (3.3) is also true for centered Hardy-Littlewood maximal function.…”
Section: By Changing Of Variablesmentioning
confidence: 91%
“…(3.5) is true for centered Hardy-Littlewood maximal function. On the other hand, using the limiting weak type behavior for maximum function in [7], (3.3) is also true for centered Hardy-Littlewood maximal function.…”
Section: By Changing Of Variablesmentioning
confidence: 91%
“…As we mentioned before [31,32], Ω ∈ L log L(S n−1 ) is a sufficient condition to guarantee the weak-type (1, 1) boundedness of T Ω . However, both the results of Janakiraman [23], Ding and Lai [11] were obtained under certain smoothness conditions. Therefore, one may ask, whether these smoothness conditions can be removed.…”
Section: Introductionmentioning
confidence: 90%
“…In 2004, Janakiraman [22] considered the Riesz transform and the singular integral operator T Ω . It was shown that the constant To explore the lower bounds of T Ω L 1 →L 1,∞ , in 2006, under the same kernel conditions, Janakiraman [23] gave the following limiting weak-type behavior for T Ω :…”
Section: Introductionmentioning
confidence: 99%
“…To explore the lower bounds of M L 1 →L 1,∞ , in 2006, Janakiraman [12] considered the following limiting weak-type behavior for the Hardy-Littlewood maximal operator M :…”
Section: Introductionmentioning
confidence: 99%